The Islamic ethical principles and Maqasid al-Shariah to enhance digital competency among adolescents - Ahmad, Noorlila; Ma, Mohamad Karimi; Abd. Rahman, Siti Fatimah; Syed Mahmood, Syarifah Rohaniah; Muhamad@ Razak, Nor Asiah; Mohamad, Syamsul Nor Azlan (Penerbit UTM Press, 2025)
Modern advancements, including computers, smart devices, high-speed internet and generative artificial intelligence, have made technology an integral part of adolescents' daily lives. The digital age has significantly transformed how they engage with technology, reshaping the ways they learn, communicate and interact. As digital environment become essential to their social and educational development, the need for digital competency has grown. However, digital competency should go beyond technical skills, incorporating ethical decision-making, identities and responsible online behavior. This article explores the integration of the Islamic ethical and Maqasid al-Shariah (the objectives of Islamic law) framework to enhance digital competency among adolescents. By focusing on the core Islamic principles such as adab (proper conduct), amanah (trustworthiness), ihsan (excellence) and niyyah (intention). The article demonstrates how these values guide adolescents in engaging with digital technologies responsibly. Furthermore, the objectives of the Maqasid al-Shariah focus on the preservation of religion (din), life (nafs), intellect (aql), lineage (nasl) and property (mal) will provide a holistic approach that ensures digital practices promote the well-being of individuals and society. This framework encourages adolescents to use digital platforms ethically, protect their personal integrity, rights, responsibilities, well-being and contribute positively to the community. The article highlights how aligning digital behavior with these Islamic values fosters both technical proficiency and a sense of social responsibility. Ultimately, holistic Islamic ethical principles and Maqasid al-Shariah into digital literacy education supports the personal, social and spiritual growth of adolescents. Thus, promoting a balanced approach to digital engagement that contributes to the broader goals of Islamic ethics and societal well-being.